PENGARUH ONLINE CUSTOMER REVIEW DAN CUSTOMER RATING TERHADAP MINAT BELI PRODUK FASHION PADA MARKETPLACE SHOPEE DI KOTA CIMAHI - Adhitya Purwa Rahardjo; Frido Saritua Simatupang (ITB AAS Indonesia Surakarta, 2024)
One of the most popular categories on the Shopee marketplace is fashion products. This is an interesting phenomenon, because it demonstrates a change in the way that consumers behave, with a propensity to purchase fashion items online as opposed to in person. This study is to investigate how customers' decisions to buy fashion items on the Shopee marketplace platform in Cimahi City are influenced by online reviews and customer assessments. Using a quantitative methodology, this study examines the validity of the instruments, tests conventional hypotheses, multiple linear regression analysis, hypothesis testing, and evaluation of the coefficient of determinatio. Participants in this study were Cimahi City residents, totaling 107, who were chosen using G-Power software based only on their intention to purchase fashion items from Shopee. This study reveals that the coefficient of determination value obtained is 0.512, which indicates that online customer reviews and customer ratings contribute 51.2% to interest in purchasing. Meanwhile, the remaining 0.488 or 48.8% was influenced by other factors not included in this study. Keywords : Online Customer Review, Cutomer Rating, Purchase Interest